Влияние продолжительности питания личинок мухи комнатной (Musca domestica L.) на ее развитие и состояние жирового тела - Карпенко, Л.В. (Вестник зоологии, 1976)
The young Musca domestica larvae may exist without food for a long time. At prolong fasting their fatty body is not destroyed, trophocytes became only many times as small in size, not only all reserves but even some cytoplasmic components of cells are consumed. When nutrition is resumed, trophocytes are again replenished by reserves and larvae quickly complete their metamorphosis forming dwarf imago. The posibility to complete rapidly the development and formation of small pupae during fasting of the elder larvae is one of the important manifestations of the species ecological plasticity.